Gentamicin- and Cephalothin-Associated Rises in Blood Urea Nitrogen - Fanning, W. Lee (1976)
Standardized rates of drug-attributed rises in blood urea nitrogen were 8.6%, 2.9%, and 9.3%, respectively, in patients receiving gentamicin alone, cephalothin alone, and both drugs together. These results provide evidence against a substantial synergism between the two drugs in the production of impaired renal function.